Animal Encounters in Valerius Flaccus' Argonautica - Mackay, Anne Elyse Tuttle, (Mnemosyne, Supplements ;, 2022)
This first in-depth study of Valerius Flaccus' animals reveals their role in his poetic programme and the manifold ways in which he establishes their subjectivity. In one encounter, a trapped bird becomes a tragic victim, while the trapper is dehumanized. Elsewhere there are touching portrayals of animal/human camaraderie and friendship. Furthermore, Valerius' provocative consideration of the 'monstrous' challenges simplistic definitions of any being's nature, or the nature of relationships across species. His challenge entails profound ethical implications for his Roman readership, which resonate with us as we assess our own relationship to animals and the natural world today.